2004
DOI: 10.1097/01.ogx.0000119184.27552.59
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antenatal Cytokine Production and the Development of Atopy and Asthma at Age 6 Years

Abstract: There is mounting evidence that antenatal factors could be important in children who develop atopy and asthma. Immunologic processes appear to operate in early infancy when challenged by exposure to environmental allergens. One possible mechanism is an alteration in cytokines, which are produced in the placenta throughout gestation and serve to protect the placenta by controlling local immunologic events. The investigators measured levels of several cytokines in cord blood in a prospective birth cohort of 407 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 0 publications
1
41
1
1
Order By: Relevance
“…Such mechanisms may include reduced or absent labor in children born by cesarean section and non-passage through the birth canal during birth. Labor has been associated with alteration of neonatal immune responses (e.g., reduced lymphocytes and CD4+ helper T cells, and increased IL-6) 49,50 . In rodents, oral exposure to lipopolysaccharide during vaginal birth triggers activation of gut epithelial cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Such mechanisms may include reduced or absent labor in children born by cesarean section and non-passage through the birth canal during birth. Labor has been associated with alteration of neonatal immune responses (e.g., reduced lymphocytes and CD4+ helper T cells, and increased IL-6) 49,50 . In rodents, oral exposure to lipopolysaccharide during vaginal birth triggers activation of gut epithelial cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the two cytokines IFN-γ and IL-13, which we analyzed in this study, are of interest. Production of IFN-γ (Th1 cytokine) in unstimulated CBMC was associated with a lower risk of atopic diseases in childhood (11). As a critical Th2 cytokine, IL-13 secretion is increased in the mucosa of atopic and non-atopic asthmatics compared with non-asthmatic controls (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted the possible influence of the in utero environment and fetal/maternal interactions on the development of atopy and asthma (4 -6). Macaubas et al (7) showed the relevance of immunological processes during early infancy, when the immature immune system is first directly exposed to environmental allergens, for the establishment of long-term patterns of responsiveness. They demonstrated that the prenatal cytokine environment, within which T cells develop, determines the degree of immune competence at birth and during early infancy.…”
mentioning
confidence: 99%